GENETIC AND MORPHOLOGICAL APPROACHES DISTINGUISH THE THREE SIBLING SPECIES OF THE ANISAKIS SIMPLEX SPECIES COMPLEX, WITH A SPECIES DESIGNATION AS ANISAKIS BERLANDI N. SP FOR A. SIMPLEX SP C (NEMATODA: ANISAKIDAE) - MATTIUCCI, Simonetta; Paolo Cipriani; Stephen C. Webb; Michela Paoletti; Federica Marcer; Bruno Bellisario; David I. Gibson; Giuseppe Nascetti (Journal of Parasitology, 2014)
Numerous specimens of the 3 sibling species of the Anisakis simplex species complex (A. pegreffii, A. simplex (senso stricto)), and A. simplex sp. C) recovered from cetacean species stranded within the known geographical ranges of these nematodes were studied morphologically and genetically. The genetic characterization was performed on diagnostic allozymes and sequences analysis of nuclear (internal transcribed spacer [ITS] of ribosomal [r] DNA) and mitochondrial (mitochondrial [mt] DNA cox2 and rrnS) genes. These markers showed (1) the occurrence of sympatry of the 2 sibling species A. pegreffii and A. simplex sp. C in the same individual host, the pilot whale, Globicephala melas Traill, from New Zealand waters; (2) the identification of specimens of A. pegreffii in the striped dolphin, Stenella coeruleoalba (Meyen), from the Mediterranean Sea; and (3) the presence of A. simplex (s.s.) in the pilot whale and the minke whale, Balaenoptera acutorostrata Lacepede, from the northeastern Atlantic waters. No F1 hybrids were detected among the 3 species using the nuclear markers. The phylogenetic inference, obtained by maximum parsimony (MP) analysis of separate nuclear (ITS rDNA region), combined mitochondrial (mtDNA cox2 and rrnS) sequences datasets, and by concatenated analysis obtained at both MP and Bayesian inference (BI) of the sequences datasets at the 3 studied genes, resulted in a similar topology. They were congruent in depicting the existence of the 3 species as distinct phylogenetic lineages, and the tree topologies support the finding that A. simplex (s.s.), A. pegreffii, and A. berlandi n. sp. (-A. simplex sp. C) represent a monophyletic group. The morphological and morphometric analyses revealed the presence of morphological features that differed among the 3 biological species. Morphological analysis using principal component analysis, and Procrustes analysis, combining morphological and genetic datasets, showed the specimens clustering into 3 well-defined groups. Nomenclatural designation and formal ...